Development of 48-condition buffer screen for protein stability assessment - Houser, Josef; Kosourova, Jana; Kubickova, Monika; Wimmerova, Michaela (European biophysics journal, 2021)
The determination of a suitable buffer environment for a protein of interest is not an easy task. The requirements of advanced techniques, the demands on the biological material and the researcher time needed for buffer optimization, as well as personal inflexibility, lead frequently to the use of sub-optimal buffers. Here, we demonstrate the design of a 48-condition buffer screen that can be used to determine an appropriate environment for downstream studies. By the combination of several techniques (differential scanning fluorimetry, dynamic light scattering, and bio-layer interferometry), we are able to assess the protein stability, homogeneity and binding activity across the screen with less than half a milligram of protein in 1 day. The application of this screen helps to avoid unsuitable conditions, to explain problems observed upon protein analysis and to choose the most suitable buffers for further research. The screen can be routinely used as a primary screen for buffer optimization in labs and facilities.
Keywords: stabilita proteinů; Protein Stability; pufry; Proteins; Fluorometry; Dynamic Light Scattering; fluorometrie; proteiny; dynamický rozptyl světla; Buffers